2021
DOI: 10.1038/s41522-021-00252-1
|View full text |Cite
|
Sign up to set email alerts
|

Coral reef biofilm bacterial diversity and successional trajectories are structured by reef benthic organisms and shift under chronic nutrient enrichment

Abstract: Work on marine biofilms has primarily focused on host-associated habitats for their roles in larval recruitment and disease dynamics; little is known about the factors regulating the composition of reef environmental biofilms. To contrast the roles of succession, benthic communities and nutrients in structuring marine biofilms, we surveyed bacteria communities in biofilms through a six-week succession in aquaria containing macroalgae, coral, or reef sand factorially crossed with three levels of continuous nutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 102 publications
(132 reference statements)
0
9
0
Order By: Relevance
“…These biogeochemical influences enrich distinct microbial taxa in reefs relative to the ocean, a pattern demonstrated in reefs across the globe (Frade et al 2020, McCliment et al 2012, Weber et al 2020b. Additionally, inputs of microbes from land sources (e.g., streams, runoff, and groundwater) and from the microbiomes of the diverse fauna that make up the benthic community further influence microbial signatures in reef environments (Quinlan et al 2019, Remple et al 2021, Wilkins et al 2019.…”
Section: Microbial Community Seascapes On Coral Reefsmentioning
confidence: 97%
See 1 more Smart Citation
“…These biogeochemical influences enrich distinct microbial taxa in reefs relative to the ocean, a pattern demonstrated in reefs across the globe (Frade et al 2020, McCliment et al 2012, Weber et al 2020b. Additionally, inputs of microbes from land sources (e.g., streams, runoff, and groundwater) and from the microbiomes of the diverse fauna that make up the benthic community further influence microbial signatures in reef environments (Quinlan et al 2019, Remple et al 2021, Wilkins et al 2019.…”
Section: Microbial Community Seascapes On Coral Reefsmentioning
confidence: 97%
“…Bioturbation and digestion by various invertebrate scavengers ensure that the sand does not accumulate decomposing organic matter, limiting the successional stagnation of the biofilms (Williamson et al 2021). Biofilm structure and function in reefs are driven largely by the composition of benthic exudates released locally (Remple et al 2021) and in this way may link the benthic producers and invertebrate consumers through the structure and function of sand biofilm communities.…”
Section: Microbe-dissolved Organic Matter Interactions Facilitate Ree...mentioning
confidence: 99%
“…Hypothesizing that these more "polluted" conditions represent more nutrient-rich environments for microbial growth, blooms of opportunistic prokaryotes responding to localized nutrient-enrichment may at least partially explain some of the differences that we observed between microbial biofilms associated with apparently healthy and SCTLD-infected corals. Nutrient enrichment has previously been shown to significantly influence marine biofilm microbial communities, though not as much as other variables such as exposure to different macroorganisms (Remple et al, 2021). However, looking exclusively at biofilms formed in association with corals, Remple et al (2021) found that nutrient enrichment resulted in an increase in species richness and a decrease in species evenness, as well as increases in Flavobacteriaceae, a family which was considerably more enriched in diseased compared to healthy mesocosms (average n = ~4,260 and 121 reads, respectively) and which we do see represented within our SCTLD-obligate-andspecific ASVs (ASVs 35 and 236).…”
Section: Discussionmentioning
confidence: 99%
“…Nutrient enrichment has previously been shown to significantly influence marine biofilm microbial communities, though not as much as other variables such as exposure to different macroorganisms (Remple et al, 2021). However, looking exclusively at biofilms formed in association with corals, Remple et al (2021) found that nutrient enrichment resulted in an increase in species richness and a decrease in species evenness, as well as increases in Flavobacteriaceae, a family which was considerably more enriched in diseased compared to healthy mesocosms (average n = ~4,260 and 121 reads, respectively) and which we do see represented within our SCTLD-obligate-andspecific ASVs (ASVs 35 and 236). This suggests that the apparent water quality deterioration observed in some diseased mesocosms may indeed have resulted in a nutrient shift that impacted the resulting mesocosm and biofilm microbial communities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation